A proposed assessment scheme for smart sustainable urban development - Elfiky, Ilham Abdelfattah (AUC Knowledge Fountain, 2019)
The twenty-first century belongs to the cities. For the first time in history, more than 50% of the world's population now lives in a city and the urban population is expected to double by 2050. The opportunities created by new technologies challenge the way in which we conceive our cities, how we plan, design and construct them and how we will live in them. The current large gap between smart city and sustainable city frameworks implies that there is a need for developing their frameworks further or re-defining the smart sustainable city concept, which is relatively new and can be seen as a successor of information city, digital city and sustainable city. Furthermore, rating standards like LEED and (GPRS) do not cover all the topics behind the Smart Sustainable City Concept. The aim of this study is to conduct and perform qualitative and comparative analysis of International Standards and case studies, to provide a foundation for developing a framework for the planning of a Smart Sustainable City based on rigorous criteria and sub-criteria. This framework, can be used to assess the smart sustainable urban development of the new administrative capital of Egypt. The criteria have been selected according to international standards via ISO37120 and the Focus Group of Smart Sustainable Cities of International Telecommunication Union (ITU-T FGSSC), as a base for the framework. The framework developed in this study is more oriented towards achieving aspects of urban life at the design and planning stage versus other models existing in the literature that are more oriented towards progress in International Communication Technology (ICT) as a dimension by itself and as means to transform already built cities to smart cities. The proposed study is intended to build up and complement key dimensions that were developed by ITU-TFGSSC, by adding sub-dimensions and key indicators filling this gap in research. The outcome of this study could be used to generate a framework and develop recommendations that has been tailored for urban planners, owners, operators and occupiers, to successfully and cost effectively adopt smart sustainable solutions as they plan, design, construct, and manage future cities. City assessment tools can be used as support for decision making in urban development as they provide assessment methodologies for cities to show the progress towards defined targets.